Strategi Guru PAI dalam Pembelajaran Al-Qur’an Siswa di SD Negeri Se-Kota Subulussalam - Yuli Zamzah Farliati; Mukhsin Nyak Umar; Yusra Jamali (Tadabbur: Jurnal Peradaban Islam, 2023)
This study aims to investigate the strategies used by Islamic Religious Education (PAI) teachers in learning the Qur'an in public elementary schools in Subulussalam City. This study involved PAI teachers as participants and elementary school students as research subjects. The method used is qualitative research with a case study approach. This study involved data collection through classroom observation, interviews with Islamic Religious Education teachers, and analysis of documents related to learning the Qur'an. The data collected was then analyzed using an inductive approach, by identifying the learning strategies used by PAI teachers and exploring their effectiveness in facilitating students' understanding and appreciation of the Qur'an. The results of the study show that there are various strategies used by PAI teachers in learning the Qur'an at SD Negeri Sekota Subulussalam. These strategies include using a variety of teaching materials, using interesting learning media, using information technology, using interactive discussion and question-and-answer methods, and giving assignments and projects related to the Qur'an. These strategies aim to facilitate students' understanding, appreciation, and practical application of the teachings of the Qur'an. Nevertheless, this study also identified several obstacles faced by Islamic Religious Education teachers in implementing Al-Qur'an learning strategies. These obstacles include limited time for learning, limited quality learning resources, and challenges in motivating students to study the Qur'an seriously.